PENGARUH KOMPETENSI, DUE PROFESSIONAL CARE, PENGALAMAN KERJA, DAN BESARAN FEE AUDIT PADA KUALITAS AUDIT - Pranadata, I Nyoman Wisnu Bayu; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
Issues concerning the poor quality of audit into the public spotlight in recent years, this was due to the involvement of the public accountant in it. This study aims to determine the effect of competence, Due professional care, work experience, and the amount of audit fees in the audit quality. This research was conducted at the KAP listed on IICPA 2015. The sample was selected using sampling techniques saturated. Data obtained by distributing questionnaires to the auditor and the analytical techniques used is multiple linear regression. Based on the analysis, known competence, due professional care, work experience, and the amount of audit fee positive effect on audit quality. Four variables were able to explain the changes in audit quality by 61.9% while the remaining 38.1% is explained by other variables not input in the research model.
Keywords: Competence, Due Professional Care, Work Experience, Magnitude Fee, Quality Audit